Unlocking the treasure trove: How can Luhmann's theory of trust enrich trust research?. Issue 1 (2nd January 2019) - Kroeger, Frens
ABSTRACT: This contribution takes the 50th anniversary of the original edition of Vertrauen, and the publication of a new translation of Trust and Power, as an opportunity to reconsider Niklas Luhmann's contribution to, and further promise for, trust research. It demonstrates the manifold ways in which Luhmann's insights can inform trust research, without therefore having to subscribe to Luhmann's systems theory as a whole. It focuses on five thematic fields in particular: the fundamental significance of trust, interpersonal vs. system trust, the relationship of trust and distrust, trust as a distinctly social phenomenon, and the relationship of trust and power. For each of these, it finds that while some aspects of Luhmann's contribution have experienced widespread (if not always explicit) adoption already, others have remained underresearched and hold great promise for further study, making Luhmann's theory a veritable 'treasure trove' for trust research.